MENGGALI POTENSI HERITAGE KAMPUNG WISATA SUKADIRI SEBAGAI DAYA TARIK WISATA - Chotibul Umam (Jurnal Manajemen dan Bisnis, 2023)
This research focuses on examining the potential of Sukadiri tourist village as a heritage tourism attraction, the goal is to realize the mission of Sukadiri tourist Village, which is to become a Tourism village to improve the welfare of the local community. This study has a limited scope in identifying the existing conditions of tourism in Sukadiri tourist village. Data collection techniques in this research are observation, in-depth interviews, documentation and literature study. The data analysis technique used is descriptive qualitative referring to the 4A component of tourism products. The results of this study are in the form of existing conditions that refer to the 4A tourism product components, namely Attraction, Accessibility, Amenity and Anciliary. The results showed that the tourism potential of Sukadiri village has heritage potential, natural tourism, creative economy and artificial. Other tourism support in the form of adequate accessibility, but on the amenity side for supporting tourism has not been well managed. Ancialry, meanwhile, is still not running well, so it needs institutional strengthening as well as increasing the capacity of local human resources in managing Sukadiri tourist village. Keywords:Potential1;Heritage2; Tourist Village3